Mutações no gene osteoprotegerina (TNFRSF11B) estão associadas com a anquilose da articulação temporomandibular - Corso, Paola Fernanda Cotait de Lucas (2020)
This study was aimed to investigate genetic variations in the osteoprotegerin-encoding gene (TNFRSF11B) in patients with Temporomandibular Joint Ankylosis (TMJA) in order to understand the genetic etiology of this condition. The sample was comprised of 17 patients diagnosed with TMJA, of both sexes with age ranging from 6 to 57 years old. TNFRSF11B mutational analysis was performed by Sanger sequencing using DNA extracted from oral epithelial cells, and the functional impact prediction of the identified variants was assessed by bioinformatic analysis. Sequencing analysis identified 15 (88.23%) patients that presented at least one genetic variant in TNFRSF11B. The mutation rs202090603 (p.E33K) was found in 6 individuals, and rs140782326 (p.V281M), rs11573942 (p.L295) and rs1375250340 (p.I389T) were identified in 1 subject each. The common singlenucleotide polymorphisms (SNPs) rs2073618 (p.N3K) and rs2228568 (p.L256) were found in 10 and 6 patients, respectively. According to the pathogenicity potential of mutations, 3 variants were considered of low impact (rs2073618, rs202090603 and rs2228568) and 3 as disease-causing (rs140782326, rs11573942 and rs1375250340). The variant rs202090603 (p.E33K) was found in the first cysteine domain and the in silico analysis showed differences in the loop positions of p.E33K mutated 3-D structure of the osteprotegerin. Our findings suggest that two polymorphisms (rs2073618 and rs2228568) and the mutations rs202090603 (p.E33K), rs140782326 (p.V281M), rs11573942 (p.L295) and rs1375250340 (p.I389T) in TNFRSF11B gene are associated with TMJA.